The The Literary Structure of the Flood Account in the Animal Apocalypse - Drawnel, Henryk (The Biblical Annals, 2023)
This article discusses the literary structure of the flood account (1 En. 89:1b–9) in the Animal Apocalypse (1 En. 85–90). Since the Qumran Aramaic text of the story (4Q206 frags. 8 I and 9) has preserved a shorter text than that found in the ancient Ethiopic version, the study of the literary additions found therein is also undertaken. Although the Aramaic text of the flood account is not free from some redactional elaborations of the literary structure of the story, the literary additions in the Ethiopic version expand the shorter structure, especially in the first part of the account (strophes 2–4). The insertion of new cosmic elements into the story (heavenly roof and earthly enclosure) creates a well-circumscribed space where the punishment of humanity, sons of the Watchers and animals by the waters of the flood takes place (strophe 4). Thus, the Ethiopic longer recension of the flood account is far more distant from the shorter text of 4Q206. The last part of this study takes a closer look at the literary context of the flood story that closes the first part of the Animal Apocalypse (1 En. 85:3b–89:9) and preannounces its second section (1 En. 89:10–90:19) marred by the shedding of blood and violence between the nations and Israel.